Análisis de la planificación del mantenimiento y su incidencia en los fallos de sistemas y componentes en las aeronaves Boeing de la Fuerza Aérea Ecuatoriana - Latacunga 2015. Diseño del programa de confiabilidad de aeronaves. - Hurtado Castellanos, Kleber Oswaldo (2015)
This work presents a study that aims, the evaluation of the maintenance management in Boeing aircraft of the Ecuadorian Air Force, to respond to the continuing failure in the components and systems, and optimizing the operation of their equipment ensuring high availability and reliability. In the investigation the maintenance planning system was analyzed, collecting data information in different areas of the organization and determining its impact on the increase of failures in the aircraft Boeing of FAE, then design a proposal for improvement. The proposed study is presented as a non-experimental research, that at the beginning, it the field mode, it uses such as: survey, observation and document review, in order to assess the management of maintenance carried out by the center, CPCM. Subsequently this job present proposed of improvement, designing the reliability program. This work allowed to obtain information of the current maintenance management and how this could be improved by a tool to control failures. So it becomes a major contributor to the development of the organization. It was concluded that maintenance management is in an acceptable condition, having a system with certain weaknesses that make it vulnerable to deviations. Thus it, evidenced the knowledge of the methods and planning systems by the collaborators and commitment to the initiation of them, with opportunities to continue improving to get high quality standards. Finally, it was designed a reliability program which includes failure monitoring in the systems and components in the 727-200 and 737-200 Boeing aircraft, and possible strategies for improve maintenance scheduling. Its implementation increase the availability and safety in operations.